Adverse respiratory outcomes among head and neck cancer survivors in the Utah Cancer Survivors Study. Issue 4 (13th November 2019) - Kawakita, Daisuke; Abdelaziz, Sarah; Chen, Yuji; Rowe, Kerry; Snyder, John; Fraser, Alison; Smith, Ken; Herget, Kimberly; Deshmukh, Vikrant; Newman, Michael; Monroe, Marcus; Hashibe, Mia
Abstract : Background: The number of head and neck cancer (HNC) survivors has been increasing because of improving survival in the United States. The aim of this study was to evaluate the incidence of respiratory disease diagnoses in HNC survivors in comparison with cancer‐free individuals. A second aim was to investigate risk factors for respiratory disease among HNC survivors. Methods: Patients with HNC diagnosed from 1996 to 2012 were identified in the Utah Cancer Registry (n = 1901). Up to 5 cancer‐free individuals from the general population (n = 7796) were matched to each HNC survivor by birth year, sex, birth state, and follow‐up time. Electronic medical records and statewide health care facility data were used to identify a disease diagnosis after the cancer diagnosis. Cox proportional hazards models were used to estimate the risks of respiratory diseases. Results: The median follow‐up times were 4.5 years for HNC survivors and 7.8 years for the general population cohort. The risks of respiratory infection (hazard ratio [HR], 1.63; 95% confidence interval [CI], 1.40‐1.90), chronic obstructive pulmonary diseases and bronchiectasis (HR, 2.65; 95% CI, 2.13‐3.29), and aspiration pneumonitis (HR, 6.21; 95% CI, 3.98‐9.68) were higher among HNC survivors than the general population cohort more than 5 years after the cancer diagnosis. Age at diagnosis, baseline body mass index, sex, baseline smoking status, treatment modality, primary site, and stage were associated with the risk of adverse respiratory outcomes among HNC survivors. Conclusions: The risk of adverse respiratory outcomes was much higher among HNC survivors than the general population cohort. Multidisciplinary care is needed to prevent the occurrence of adverse respiratory outcomes among HNC survivors. Abstract : The risk of adverse respiratory outcomes among head and neck cancer survivors has been investigated, and it has been found to be much higher than the risk in a matched general population cohort. Therefore, multidisciplinary care is needed to prevent the occurrence of adverse respiratory outcomes among head and neck cancer survivors.